Muhammad Sebagai Pemimpin Agama dan Negara - Ahmad Fadholi (Misykah : Jurnal Pemikiran dan Studi Islam, 2020)
Muhammad is a great human figure, the messenger of God who was given the mandate to deliver the message, or teachings of God, which became known as the teachings of Islam. His noble character attracted the sympathy of the Arab community at that time, even though some people were uneasy about his existence. As a chosen human, he is equipped with knowledge and abilities. God also gave him a noble position among humans by giving him the title of prophecy. This noble position shows that he is truly the messenger of God. In addition, the expertise of the Prophet Muhammad and his belief in the eyes of the people in regulating, maintaining, developing the territory, building cities, giving attention, peace, welfare and progress of society, made him worthy of being called a "statesman". In implementing teachings, regulating the wheels of life and government, he applies the values ​​of Islamic teachings and also the principle of compassion for all nature. Abstrak Muhammad adalah sosok manusia agung utusan Tuhan yang diberikan amanah menyampaikan risalah, atau ajaran Tuhan, yang kemudian dikenal dengan ajaran Islam. Akhlaknya yang mulia menarik simpati masyarakat arab kala itu, meskipun sebagian kalangan resah dengan keberadaannya. Sebagai manusia pilihan, ia dibekali dengan ilmu dan kemampuan. Tuhan pun memberikan kedudukan mulia di antara manusia dengan memberikannya gelar kenabian. Kedudukan mulia ini menunjukkan bahwa ia adalah benar-benar sang utusan Tuhan. Selain itu, kepiawaian Nabi Muhammad dan kepercayaannya di mata masyarakat dalam hal mengatur, menjaga, mengembangkan wilayah kekuasaan, membangun kota-kota, memberikan perhatian, kedamaian, kesejahteraan serta kemajuan masyarakat, menjadikannya layak disebut sebagai “negarawan”. Dalam mengimplementasikan ajaran, mengatur roda kehidupan dan pemerintahan, ia menerapkan nilai-nilai ajaran Islam dan juga prinsip kasih sayang terhadap seluruh alam.